Multistate APLIP and VibLIP: from molecular bond extension to atomic transport - Suominen KA (TAYLOR & FRANCIS LTD, 2025)
APLIP is a method for using a STIRAP-like three-state configuration with two laser pulses for continuous extension of a molecular bond, introduced in 1998. It is based on time-dependent light-induced potential surfaces (LIP). In VibLIP one extends the idea into a method for tailoring the vibrational state while changing the electronic state, introduced in 2000. Here I discuss the extension of both methods to situations that involve more than three electronic states, and note the possibility of using the method on adiabatic transport of atoms between microtraps or equivalent structures.